SEBUAH GAGASAN PENGEMBANGAN APLIKAISI TEKNOLOGI INFORMASI UNTUK MENDUKUNG PENDIDI KAN MAHASISWA STRATA.I BIDANG EKONOMI PERUSAHAAN - Michael Iskandar (Bina Ekonomi, 2005)
Universities  nowadays are under  increasing pressure  to produce graduates who are not only knowledgeable but who also have valuable work experience as well as excellent  interpersonal  skills. The  last  two are often lacking  in the university  graduates of today, which will be to their detriment when-they enter the workforce  looking  for good, well-paid  jobs with long- range prospects. This paper introduces an idea to include a continuous,  lT-enhanced, “work experience" simulation  in the curriculum,  in which a student will be subjected to all the experiences  an actual employee  will encounter  in an actual firm, at various operational  and management  levels.